Neutron-induced light-ion production from Fe, Pb and U at 96 MeV - S. Pomp (2018)
© Copyright owned by the author(s) under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike Licence. Double-differential cross sections for light-ion production (up to A=4) induced by 96 MeV neutrons have been measured for natFe, natPb and natU. The experiments have been performed at the The Svedberg Laboratory in Uppsala, using two independent devices, MEDLEY and SCANDAL. The recorded data cover a wide angular range (20'-160') with low energy thresholds. The work was performed within the HINDAS collaboration studying three of the most important nuclei for incineration of nuclear waste with accelerator-driven systems (ADS). The obtained cross section data are of particular interest for the understanding of the so-called pre-equilibrium stage in a nuclear reaction and are compared with model calculations performed with the GNASH, TALYS and PREEQ codes.